Chemical-Induced Cleft Palate Is Caused and Rescued by Pharmacological Modulation of the Canonical Wnt Signaling Pathway in a Zebrafish Model - Narumi, Rika; Liu, Shujie; Ikeda, Naohiro; Morita, Osamu; Tasaki, Junichi (Frontiers in Cell and Developmental Biology, 2020)
Cleft palate is one of the most frequent birth defects worldwide. It causes severe problems regarding eating and speaking and requires long-term treatment. Effective prenatal treatment would contribute to reducing the risk of cleft palate. The canonical Wnt signaling pathway is critically involved in palatogenesis, and genetic or chemical disturbance of this signaling pathway leads to cleft palate. Presently, preventative treatment for cleft palate during prenatal development has limited efficacy, but we expect that zebrafish will provide a useful high-throughput chemical screening model for effective prevention. To achieve this, the zebrafish model should recapitulate cleft palate development and its rescue by chemical modulation of the Wnt pathway. Here, we provide proof of concept for a zebrafish chemical screening model. Zebrafish embryos were treated with 12 chemical reagents known to induce cleft palate in mammals, and all 12 chemicals induced cleft palate characterized by decreased proliferation and increased apoptosis of palatal cells. The cleft phenotype was enhanced by combinatorial treatment with Wnt inhibitor and teratogens. Furthermore, the expression of tcf7 and lef1 as a readout of the pathway was decreased. Conversely, cleft palate was prevented by Wnt agonist and the cellular defects were also prevented. In conclusion, we provide evidence that chemical-induced cleft palate is caused by inhibition of the canonical Wnt pathway. Our results indicate that this zebrafish model is promising for chemical screening for prevention of cleft palate as well as modulation of the Wnt pathway as a therapeutic target.